Hubungan Obesitas dengan Kualitas Hidup Lansia Hipertensi Diwilayah Puskesmas Wonokromo Surabaya - Anatasta, Lingga; Ainiyah, Nur; Hatmanti, Nety Mawarda; Maimunah, Siti (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Hypertensive patients who are obese often find it difficult to carry out daily activities, which is why hypertensive patients with obesity have a poor quality of life. The purpose of this study was to find the relationship between obesity and quality of life in elderly hypertensive patients at the Wonokromo Health Center in Surabaya. This method uses a research design using correlation analysis. The study population was elderly aged 60-74 years with hypertension as many as 100 respondents. Using the straitfied random sampling technique, a sample size of 80 respondents was obtained. Data collection using the BMI (Body Mass Index) and WHOQOL-BREF questionnaires, has passed the ethical test at Nahdlatul Ulama University Surabaya with No. 0174/EC/KEPK/UNUSA/2023, this study used the Spearman rho test. The results showed that most of the 45 respondents (75.5%) were in the obesity category of degree 1, and of the 35 respondents the majority (51.5%) were in the category of degree 2. The results of the statistical test for the significance value of p was 0.025, it can be concluded that there is relationship between obesity and quality of life of hypertensive elderly. From this study it can be concluded that most of the elderly who are obese with degree 1 have a poor quality of life. Further research is expected to further develop by looking at and connecting other factors that affect quality of life.